Preparation and Standardization of a Stable AHF Plasma - Thelin, G. M; Los Angeles, California (Thrombosis and Haemostasis, 1968)
A stable, lyophilized AHF reference plasma has been prepared from pooled plasma from at least 50 normal healthy donors and standardized against a primary standard of fresh plasma from 20 healthy male donors aged 20 to 40. Average AHF potency of a typical lot is 98.8%, and moisture content is less than 0.5%. Under storage at -25° C, this AHF reference plasma is stable for at least 18 months. It has been used in several major coagulation laboratories, and has given consistently satisfactory and reproducible results in AHF assays.